Characterization of Awassi lamb fattening systems: a Syrian case study - Wiedemann Hartwell, Birgitte; Iñiguez, Luis; Mueller, Joaquin Pablo; Wurzinger, María; Knaus, W.F. (2017)
Intensive lamb fattening systems are evolving in developing Middle Eastern countries due to high demand for lambs at favorable prices; however, little is known about their characteristics and constraints. A survey was conducted in Syria involving 241 farmers to characterize the fattening production systems and main constraints, with emphasis on feeding, management, labor, and marketing. Most farmers (90%) considered the income from fattening to be from medium to high, and 57% expressed that lamb fattening along with alternative income sources compose the family's livelihood strategies. Fattening systems offer employment to family members. Market price was the main decision factor to buy and sell lambs, but this was only part of various marketing aspects. Male lambs usually bought at markets at the mean age of 4 months (mean weight of 31 kg) are sold after fattening at a 50–60 kg weight range. The average yearly fattening cycle was 2.7 batches, and the average number of lambs per batch was 232. For 65% (n = 241) of the farmers the major constraint to fattening was feeding cost, and for about a half of farmers (51%, n = 241), disease outbreaks and prices for veterinarian services constituted the second important constraint. Research on least-cost fattening diets and curbing disease problems to increase farmer's income margins is needed. It is expected that due to existing commonalities, the information emerging from this study regarding major constraints to Awassi lamb fattening systems could be useful for an across-synthesis on Awassi fattening production in the region